Pelatihan Dan Pemberdayaan Penyuluh Petani Di Kecamatan Suwawa Timur Da-lam Analisis Usahatani Sorghum - Arsyad, Karlena; Sirajuddin, Zulham (STMIK Royal, 2024)
Sorghum is an extraordinary commodity because of its waste-free characteristics. Almost all parts of the plant can be used, including leaves, fruit stems, and wilt. Unfortunately, the personnel at the East Suwawa BPP partners and the farmers they support still lack experience in sorghum farming, especially in profit analysis. This is an obstacle in spreading sorghum as an agricultural potential, because extension workers have difficulty providing farmers with an understanding of the benefits of sorghum farming. Therefore, knowledge is needed in carrying out farming analysis, as well as organizing human resources in farmer groups so that they can produce maximum quality and quantity. Through this knowledge and ability, it is hoped that partners can further optimize the dissemination of sorghum farming to the farmers they support so that they can produce sustainably. The methods used in this service activity are training and mentoring. For training activities, farming business analysis and farmer group management were carried out for one day, where the implementing team facilitated training to partners, namely BPP East Suwawa. After the training activities, students in the implementing team provided regular assistance for two weeks to optimize the results obtained in the training. The results of the activity showed that the activity participants were very enthusiastic during the mentoring activity, and gave positive responses, so that activities like this could be routine, especially in assisting with sorghum farming analysis. Keywords: farming analysis; sorghum; training; mentoring